Association of Virologic Failure and Nonnucleoside Reverse Transcriptase Inhibitor Resistance Found in Antiretroviral-Naive Children Infected With Human Immunodeficiency Virus and Given Efavirenz-Based Treatment. (13th June 2019) - Higa, Nikki; Pelz, Amy; Birch, Donald; Beck, Ingrid A; Sils, Tatiana; Samson, Pearl; Bwakura-Dangarembizi, Mutsawashe; Bolton-Moore, Carolyn; Capparelli, Edmund; Chadwick, Ellen; Frenkel, Lisa M
Abstract: Among 66 antiretroviral-naive children aged <3 years with human immunodeficiency virus (HIV) or coinfected with HIV and tuberculosis and initiating efavirenz-based antiretroviral therapy (ART), non–nucleoside reverse transcriptase inhibitor (NNRTI) resistance was detected before ART in 5 (7.6%). Virologic failure occurred in 2 of these children; they were last tested at 16 and 24 weeks of ART. Pre-ART NNRTI resistance was not associated with virologic failure.